DEBATE: Response to McWherter. Issue 5 (October 2015) - Assiter, Alison
Abstract : This contribution to a debate with Dustin McWherter evaluates his claim that Kant is a 'non-ontologist' or an 'anti-ontologist' and challenges one specific consequence which McWherter argues follows from this attribution to Kant. I argue that, while it is true that Kant restricts the domain of 'objects' or 'appearances' as he calls them to what is knowable, this does not make him an 'anti-ontologist'.